AI-powered banana diseases and pest detection - Selvaraj, Michael Gomez; Vergara, A.; Ruíz, H.; Safari, N.; Elayabalan, S.; Ocimati, W.; Blomme, Guy (Springer, 2019)
Banana (Musa spp.) is the most popular marketable fruit crop grown all over the world, and a dominant staple food in many developing countries. Worldwide, banana production is affected by numerous diseases and pests. Novel and rapid methods for the timely detection of pests and diseases will allow to surveil and develop control measures with greater efficiency. As deep convolutional neural networks (DCNN) and transfer learning has been successfully applied in various fields, it has freshly moved in the domain of just-in-time crop disease detection. The aim of this research is to develop an AI-based banana disease and pest detection system using a DCNN to support banana farmers.